Surviving the storm: A pragmatic non‐randomised examination of a brief intervention for disaster‐affected health and social care providers. (5th October 2022) - Powell, Tara; Scott, Jennifer; Yuma, Paula; Hsiao, Yuan
Abstract: Disasters affect the well‐being of individuals, families and communities. Health and social care providers are essential in response and recovery efforts and are among the most vulnerable to negative physical and mental health impacts of a disaster. Few evidence‐based interventions are available to address the psychological needs of providers. The aim of this study was to examine the psychological distress of health and social care providers before and after participating in the brief group intervention, Resilience and Coping for the Healthcare Community (RCHC) and its expanded version, RCHC+. We conducted a pragmatic non‐randomised cluster trial with 762 health and social care providers in south Texas and Puerto Rico post‐Hurricanes Harvey and Maria. Participants completed surveys assessing post‐traumatic stress (PTSD), anxiety, burnout and secondary traumatic stress (STS) prior to intervention delivery and at two time points post‐intervention. We calculated the frequency of symptom cut‐off scores at baseline, then estimated multilevel ordinal models to examine changes in symptoms across time. Prior to participation in the RCHC (approximately 12 months after the hurricanes), providers reported high levels of PTSD, anxiety and STS symptoms. After participation, providers in both intervention conditions reported a significant reduction in PTSD symptoms from baseline that was sustained over both time points. The likelihood of a reduction in symptoms of anxiety and STS from baseline was sustained at both time points for participants in the RCHC+ condition. These findings indicate that both the RCHC and RCHC+ interventions may reduce psychological distress for health and social care providers and could be an important part of advance planning to support provider's mental health during and after a disaster. Further examination of the RCHC in other disaster contexts could provide additional insight into the responsiveness of the intervention to reducing psychological distress symptoms.